A comparative study of PPIUCD acceptance between primiparaous and multiparaous women in a tertiary care hospital in Tamil Nadu - Ramya, K. S.; Meena, T. S.; Mothilal, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum intrauterine contraceptive device (PPIUCD) is a postpartum family planning method which provides spacing to the next pregnancy and also it helps to avoid unwanted / unintended pregnancy during postpartum period. Our aim is to study the willingness and PPIUCD acceptance between primiparaous and multiparaous women and compare them as a factor of route of insertion (vaginal versus caesarean). Methods: 1060 vaginal and caesarean deliveries conducted over a period of three months and 676 PPUCD insertions was done among the deliveries in a tertiary care hospital. A comparative cross-sectional study was done on the acceptance of PPIUCD by postpartum mothers between primiparous and multipararous women among the deliveries for the study period. Results: The proportion of willingness for PPIUCD was 68.8% among the postpartum mothers. The percentage of acceptance of PPIUCD was 73.8% and 51.4% in respect of primiparous and multiparous postpartum mothers. The route of PPIUCD insertion was more in caesarean deliveries (34.1%) than in vaginal deliveries (29.7%) in the total deliveries. The PPIUCD insertion in primiparous women was effective and statistically significant at p-value is <0.05. Conclusions: PPIUCD is a strong weapon in the family planning and should be encouraged in both vaginal and caesarean deliveries. The acceptability of PPIUCD by postpartum mothers was more in primiparous than in multiparous women.